Illustrations of the Huttonian Theory of the Earth - Playfair, John, 1748-1819 (Salt Lake City, UT : Project Gutenberg, 2022)
"Illustrations of the Huttonian Theory of the Earth" by John Playfair is a scientific publication written in the early 19th century. The book aims to elucidate and popularize the geological theories of James Hutton, emphasizing the processes that have shaped the Earth over time. Playfair seeks to explain concepts related to the formation of rocks, the phenomena of stratified and unstratified bodies, and the evidence for various geological processes, making it an accessible text for those seeking to understand Hutton's ideas. The opening of the treatise introduces the author's goals and sets the stage for an extensive exploration of geological concepts. Playfair discusses the necessity of a clear and comprehensive theory of the Earth, addressing the complexities of geology as a relatively new scientific discipline. He contrasts Hutton's views with prevalent theories of his time, namely those favoring either fire (volcanic) or water (aqueous) as definitive agents in geological formation. Playfair's analysis begins with the materials of strata, hinting at forthcoming discussions on their consolidation and positioning, and underscores his belief that past geological processes are critical for understanding the present state of the Earth. (This is an automatically generated summary.)
Release date is 2022-02-06
Tom Cosmas produced from materials made available at The Internet Archive and placed in the Public Domain.
Keywords: Geology; Hutton, James, 1726-1797. Theory of the earth